PROVERBS IN COMPARISON AND CONTACT: EXAMPLES FROM THE PROVERBIAL DISCOURSE OF THE BALKANS - Tserpes, Georgios (Proverbium - Yearbook, 2024)
Comparison is an inherent process in folkloristics. The inclusion of paremiology in folklore studies and the concept of proverb being a folklore genre allows the comparison of proverbs too, which are most suitable for a study of this kind. However, what needs to be defined is what comparison consists of and how it differs from other approaches like those of contrast and typology. In this paper we will try to highlight this concept and see how it is related to variation, a key feature to folklore, using examples from the proverbial discourse of the Balkan peoples. The methodology employed in this study revolves around establishing specific criteria for determining comparability among proverbs, while the examples mentioned are taking into account both the etic and the emic view regarding the interpretation of the proverbial material. The examples selected illustrate proverbs that are either directly comparable or perceived as equivalents by the folk themselves, evident in their integration into daily discourse.